Pengaruh Penerapan Manajemen Rantai Pasok dan Sistem Erp pada Perusahaan Tesla Inc - Febriani Fajar Wati; Roby Tan; Mashita Ayuni; Melvin Louisly; Melvin Sihombing; Elza Theofhilia (Serat Acitya, 2022)
The United States is home to Tesla Inc., a manufacturer of auto parts. For efficient operation, Tesla Inc. must implement a supply chain management plan. In this section, we will assess the use of enterprise resource planning (ERP) in supply chain management at Tesla Inc. Tesla Inc. supply chain management based on a vertical supply chain integration strategy. Likewise, Tesla Inc. uses a self-designed enterprise resource planning (ERP) system called WARP to interconnect enterprise processes